Optimal nuclear trigeneration system considering life cycle costing - Khairulnadzmi, Jamaluddin; Sharifah Rafidah, Wan Alwi; Zainuddin, Abdul Manan; Khaidzir, Hamzah; Klemeš, Jiří Jaromír; Roziah, Zailan (Elsevier Ltd, 2022)
A nuclear reactor can generate a large amount of high-temperature waste heat, which can be recovered to produce simultaneous electricity, heating and cooling, known as a trigeneration system. Trigeneration System Cascade Analysis is a methodology based on Pinch Analysis to optimise a centralised trigeneration system in various energy ratings in demands. However, the previous study does not consider a complete life cycle costing in the Trigeneration System Cascade Analysis. The methodology consists of three main parts, which are data extraction, development of Trigeneration System Cascade Analysis, and calculations of the life cycle costing. In this analysis, a centralised Pressurised Water Reactor, which is the most commonly used nuclear reactor in the world, is applied in a trigeneration mode in three different industrial plants. Based on the results of the case study, an optimal Pressurised Water Reactor trigeneration system is obtained where the total thermal energy required is 1,102.25 MW or translated into 26.5 GWh/d. The Equivalent Annual Cost for the case study, on the other hand, showed the centralised Pressurised Water Reactor trigeneration system requires 1.89 × 1011 USD/y for maintaining, operating, constructing, and disposing of the overall Pressurised Water Reactor trigeneration system. The maintenance cost is the highest percentage which constitutes 51.3% of the overall cost. Comparisons between normal conditions, and planned and unplanned shutdowns are also conducted, and the results show that Equivalent Annual Costs of planned and unplanned shutdowns required an additional 1.4 MUSD and 0.5 MUSD to support the deficit energy during shutdowns. The implementation of the full life cycle costing during the normal conditions planned and unplanned shutdowns of the Pressurized Water Reactor trigeneration system gives a proper projection of the cash flows that can create an economic model that reflects all the project realisation conditions.